Timing and expression of the angiopoietin-1-Tie-2 pathway in murine lung development and congenital diaphragmatic hernia - Adrienne Grzenda; John Shannon; Jason Fisher; Marc S. Arkovitz (The Company of Biologists, 2013)
SUMMARY Congenital diaphragmatic hernia (CDH) is one of the most common congenital abnormalities. Children born with CDH suffer a number of co-morbidities, the most serious of which is respiratory insufficiency from a combination of alveolar hypoplasia and pulmonary vascular hypertension. All children born with CDH display some degree of pulmonary hypertension, the severity of which has been correlated with mortality. The molecular mechanisms responsible for the development of pulmonary hypertension in CDH remain poorly understood. Angiopoitein-1 (Ang-1), a central mediator in angiogenesis, participates in the vascular development of many tissues, including the lung. Although previous studies have demonstrated that Ang-1 might play an important role in the development of familial pulmonary hypertension, the role of Ang-1 in the development of the pulmonary hypertension associated with CDH is poorly understood. The aim of this study was to examine the role of the Ang-1 pathway in a murine model of CDH. Here, we report that Ang-1 appears important in normal murine lung development, and have established its tissue-level expression and localization patterns at key time-points. Additionally, our data from a nitrofen and bisdiamine-induced murine model of CDH suggests that altered expression patterns of Ang-1, its receptor Tie-2 and one of its transcription factors (epithelium-specific Ets transcription factor 1) might be responsible for development of the pulmonary vasculopathy seen in the setting of CDH.